Analisis SWOT Financial Technology (Fintech) Pembiayaan Perbankan Syariah Di Indonesia (Studi Kasus 4 Bank Syariah Di Kota Medan) - Ridwan Muchlis (Universitas Islam Negeri Sumatera Utara, 2018)
This study wants to know the development of applications created by Islamic banking in order to be able to utilize FinTech in an effort to accelerate the financing process. This technology is expected to facilitate services to customers in terms of financing products in Islamic banks. The variety of financing products in Islamic banking requires a more applicative system to make it easier for customers to understand, understand, and use these financing products with an application. But the development of this fintech application turned out to have several disadvantages. One of them is the need for an internet network that supports the efficiency of financing activities in Islamic banks and also the existence of cyber crime activities that make the interest of customers to use this application to be reduced. This type of research is qualitative research using the SWOT analysis method on 4 Islamic banks in Medan City. Based on the results of the research analysis, it is suggested that from the outset prepare regulations relating to FinTech financing. The risk can be minimized and customers increase their understanding and knowledge for transaction convenience and security in Islamic banking.